Les entreprises et l'emploi: les nouvelles formes de qualification du travail - Doray, Pierre (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "Les entreprises et l'emploi : les nouvelles formes de qualification du travail," by Annette Dubé and Daniel Mercure,
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Job skills; Labor Unions; Qualifications; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z